The contribution of procurement audit in enhancing ethical and compliant procurement practices: A case of Sokoine University of Agriculture (SUA) - Mwarizo, Halima O. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the Degree of Masters of Business Administration (Corporate management) – MBA (CM) of Mzumbe University